EXPLORING THE RELATIONSHIP AMONG SUSPENSION OF JUDGEMENT, SEARCH FOR KNOWLEDGE, INTERPERSONAL UNDERSTANDING, ETHICAL LEADERSHIP AND INTERNAL AUDIT EFFECTIVENESS - Amad Rashid, Basariah Salim, Halimah Nasibah Ahmad (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The main objective of the present study is to assess the relationship among suspension of judgement (SJ), search for knowledge (SK), interpersonal understanding (IU), ethical leadership (EL) and internal audit effectiveness (IAE). For this purpose, the present study was conducted in the companies listed in Pakistan Stock Exchange. Two sets of questionnaires were distributed in 400 listed companies, whereas 162 completed sets in all respects with a response rate of 41% were received back. For the analysis of gathered data, PLS-3 was used as the tool. The results of the present study show that SJ, SK and EL have a positive relationship with IAE. This study fills the gap of limited studies conducted regarding audit issues, in the context of Pakistan.